Kesultanan Bima di Pulau Sumbawa - Haris, Tawalinuddin (Wacana, Journal of the Humanities of Indonesia, 2006)
Bima is a region that has been attracting researchers' attention, which should not be surprising because it has always been a multicultural region. Its history reveals that Bima was one of the sailing routes, especially of the Malay Muslim traders, sailing from the direction of East Java. Bima then became a center of the Islamic rule in the eastern Nusantara. This paper discusses a brief history of how Bima became a center of Islamic rule that was strongly influenced by the Malays.